PERAN KEPEMIMPINAN KEPALA MADRASAH TERHADAP HASIL BELAJAR SISWA MADRASAH IBTIDAIYAH - Kasto, Kasto; Suardiman, Siti Partini; Hidayati, Dian (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Student learning outcomes are a set of abilities found in students after following the learning process. This study aims to determine the role of madrasah head leadership on student learning outcomes in Wonogiri Regency Madrasah Ibtidaiyah. The leadership of madrasah principals is a key factor in creating a conducive learning environment and improving the quality of education. This research uses a quantitative approach with a survey method using a questionnaire as a data collection tool. The survey method is a method that has the aim of taking a large amount of data by taking a sample of the population using a questionnaire, where the questionnaire was distributed to 94 teachers of Madrasah Ibtidaiyah in Wuryantoro District Wonogiri Regency. Data analysis was conducted using a single regression test and SPSS software. The results showed that the leadership of madrasah principals has a significant effect on student learning outcomes. The majority of respondents rated the leadership of madrasah principals in the high category, with an average score of 80.46, while student learning outcomes were also in the high category with an average score of 63.80. Thus, this study confirms that the leadership of madrasah principals has a strategic role in improving student learning outcomes.